Orange to red emissive aldehyde substituted donor-π-acceptor phenothiazine derivatives: Optoelectronic, DFT and thermal studies - Mantur, Shivaraj; Patil, Mallikarjun Kalagouda; Nadaf, Afra Quasar Abdul Rasheed; Najare, Mahesh Sadashivappa; Yaseen, Mohammed; Nesaragi, Aravind Raviraj; Inamdar, Sanjeev Ramchandra; Khazi, Imtiyaz Ahmed; Kamble, Ravindra Ramappa (European Journal of Chemistry, 2023)
A new class of probes was synthesized using a simple and efficient synthetic protocol. These compounds (PTZ-6(a-e)) have the phenothiazine (PTZ) moiety as the electron donor (D) and substituted aldehydes along with the acrylonitrile group, which acts as the electron acceptor (A), thus making D-π-A push-pull system. The structures of the newly synthesized series of small organic target molecules PTZ-6(a-e) were investigated and confirmed by spectros-copic techniques. The optical/solvatochromic properties were studied in detail by UV-vis absorption and fluorescence spectroscopy, because the molecules have shown good solubility in organic solvents. The density functional theory (DFT) model with the CAM-B3LYP function is utilized to study the photophysical properties of the probes, as these probes exhibited orange-to-red emission. Optical band gap values ranged from 2.32 to 2.50 eV, and these probes exhibited good thermal stability with a melting temperature of 136 to 198 °C and a T5d temperature range from 335 to 354 °C. The cyclic voltammetry study confirms that the Eoxonset values of the target compounds are 0.80 eV. The quantum yields (Φ) of the probes are measured experimentally in ethanol and the Stokes shifts are observed to be in the range of 4846-9430 cm-1. The results displayed that novel (D-A-D) chromophores could play an important role in organic optoelectronics.